2002
DOI: 10.1590/s0104-66322002000400010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two cryoprotectant mixtures on frozen surubí surimi

Abstract: -"Surimi" itself is not a food; it is an intermediate phase of the production of "kamaboko"(a gel formed by the addition of salt to the surimi and direct heating to 80-90ºC) and a series of high-priced shellfish analogs. The protective effect that two cryoprotectant mixtures exerted during freezing and frozen storage of frozen surimi of surubí (Pseudoplatystoma coruscans) on the functional quality of the gels prepared was studied. The selected washing conditions selected to obtain an acceptable functional qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…(2003) also reported considerable losses of proteins and other water‐soluble components after washing. Medina and Garrote (2002) reported that about 19% of the total nitrogen corresponds to sarcoplasmic proteins, whose removal by washing benefits preservation of the muscle in the frozen state. Nowsad et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2003) also reported considerable losses of proteins and other water‐soluble components after washing. Medina and Garrote (2002) reported that about 19% of the total nitrogen corresponds to sarcoplasmic proteins, whose removal by washing benefits preservation of the muscle in the frozen state. Nowsad et al.…”
Section: Resultsmentioning
confidence: 99%
“…They found that water retention properties were protected and folding test and sensory scores were well preserved in the mince with added cryoprotectant. Medina and Garrote (2002) reported that even with the cryoprotectants, freezing decreased gel strength as it produced a decrease of almost 32% in the strength of the gel prepared with fresh surimi. However, the two cryoprotectant mixtures showed very good results during frozen storage; especially at 45 and 90 days of storage, the surimi gels with the sucrose/sorbitol mixture had a greater resistance than those with maltodextrin/sorbitol.…”
Section: Resultsmentioning
confidence: 99%
“…Medina & Garrote (2002) explained that the gel texture depends on the species of the fish used for the preparation of the surimi, well as on the concentration of the salt used for the proteins solubilization, the temperature, the time of the heat treatment and the moisture content. To Visessanguan et al (2000), the oscillations in the texture parameters may be due to the breaking of myosin, which leads to an increase in the semi gel fluidity, causing the separation of some protein grids already existent.…”
Section: Texture Profile Analysismentioning
confidence: 99%
“…The deteriorations are due to autolytic spoilage by enzymes, lipid oxidation, microbiological spoilage, or the combination of them [3,4]. Surimi or surimi products should therefore be stored in a frozen state [5]. The development of new surimi-based products that can be stored at room temperature without Fermented foods are encountered worldwide, and they are prepared from a wide variety of foods of animal, plant and micro-organism origins [6].…”
Section: Introductionmentioning
confidence: 99%